Frequency and pattern of congenital heart defects among admitted patient in a tertiary care hospital in Bangladesh - Munsi, M. Abu Sayed; Sayeed, M. Abu; Akter, Maher (International Journal of Research in Medical Sciences, 2023)
Background: Congenital heart disease (CHD) is the commonest of all congenital lesions accounting for nearly 28% of all congenital malformations that have significant impact on morbidity, mortality and heath care cost in children. The aim of study was to determine the pattern of distribution of CHD and the age at which initial diagnosis of CHD was made among children admitted under paediatric cardiology department, Bangladesh Shishu hospital and institute. Methods: This is a descriptive and prospective hospital-based study conducted in the pediatric cardiology department, Bangladesh Shishu hospital and institute. This study included all the patients admitted during January-June 2022 in pediatric cardiology department having confirmed diagnosis of CHD on basis of echocardiographic report. The collected data was entered and analyzed by using statistical package for social sciences v 24.0. Results: Out of 337 patient, 175 patient were male (51.9%) and 162 female (48.1%) with male female ratio of 1.08:1. Total 219 cases (64.9%) were acyanotic CHD and 118 (35.1%) were cyanotic congenital heart lesions. In acyanotic CHD ventricular septal defects (VSDs) constitute 38.8% followed by AV canal defect 6.7%, patent ductus arteriosus (PDA) 3.6%. In cyanotic CHD tetralogy of Fallot (TOF) was the commonest lesion accounted for 28 (8.3%) followed by d-transposition of great arteries 16 (4.7%), pulmonary atresia 15 (4.5%), total anomalous pulmonary venous circulation TAPVC 11 (3.3%), tricuspid atresia 9 (2.7%) and DORV, VSD, PS 10 (2.9%). The commonest combination was VSD with ASD in 15 cases (4.5%). Most of the patient was diagnosed in 1st year of age 280 (83.1%) Conclusions: CHD are very common in our setup and early detection of CHD is increasing. Overall burden of CHD is also increasing therefore a proper population-based study on a large scale is needed to estimate the prevalence accurately.